2016
DOI: 10.29052/ijehsr.v4.i4.2016.19-27
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Gestational Diabetes Mellitus Risk Factors in Local Population

Abstract: Background The gestational diabetes mellitus (GDM) is defined as any degree of glucose intolerance with onset or first recognition during pregnancy. Risk management of GDM should be done at first prenatal visit. As it is the most common metabolic complication of pregnancy, the present study was focused on finding out the risk factors of GDM in local population. Method We evaluated the risk factors of GDM in 200 females who were randomly tested for GDM with 75 g Oral glucose tolerance test (OGTT) at 24-28 th we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…We found that maternal age was positively associated with the frequency of GDM. A similar association had been observed in earlier studies from other parts of Pakistan by Bibi et [5][6][7][8][9][10][11][12][13] The reason given for this association is similar to the reason behind the development of T2DM, i.e. with age, the pancreas starts producing insulin less effectively.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found that maternal age was positively associated with the frequency of GDM. A similar association had been observed in earlier studies from other parts of Pakistan by Bibi et [5][6][7][8][9][10][11][12][13] The reason given for this association is similar to the reason behind the development of T2DM, i.e. with age, the pancreas starts producing insulin less effectively.…”
Section: Discussionsupporting
confidence: 85%
“…This is because GDM has an association with many factors that include family history, maternal age, parity, educational level, ethnicity, maternal occupation, polyhydramnios, history of GDM, anaemia, stress, hypertension, history of abortions, lack of exercise, pre-pregnancy weight, and G Ge es st ta at ti io on na al l D Di ia ab be et te es s M Me el ll li it tu us s i in n P Pr re eg gn na an nt t W Wo om me en n Pak Armed Forces Med J 2022; 72 (6): 2097 BMI. 12,13 These factors had not been explored in our study and this might have resulted in different results. This was also one of the limitations of our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The most common risk factors for GDM among our patients were a family history of diabetes and a prior history of abortion. This was consistent with the findings of 2 previous studies (24,25) . When comparing patients with GDM patients to women not diagnosed with GDM, only the history of obesity was found to be significantly different (p≥ 0.05) between the 2 groups, where patients with GDM had a higher history of obesity.…”
Section: Discussionsupporting
confidence: 94%
“…It is hard to correlate dyslipidemia with hypovitaminosis D when, by some estimates, up to 90% of the general population harbors some variant of suboptimal cholesterol blood levels in Pakistan 16 . Concordantly, exceptionally high rates of vitamin D deficiency have been reported all across Pakistan by multiple authors; all studies showed vitamin D deficiency disproportionately affected women [18][19][20] . Whenever patients with hypovitaminosis D have dyslipidemia, these tend to affect HDL-C levels more than LDL-C or triglyceride levels; the most common variant of dyslipidemia in the local population is due to aberrant HDL-C levels.…”
Section: Discussionmentioning
confidence: 71%